The business model navigator : the strategies behind the most successful companies - Gassmann, Oliver, 1967-; Frankenberger, Karolin; Choudury, Michaela (Harlow, England : Pearson, 2020)
The method, the Business Model Navigator, consists of 55+ successful business model patterns, which can serve as blueprints for your own business model innovation efforts. The present work specifically addresses practitioners and consciously avoids complicated theoretical arguments. The purpose of this book is to introduce a methodology - the Business Model Navigator - that will help innovate business models in a structured manner.
Includes bibliographical references and index.
Keywords: Business planning; New business enterprises; Entrepreneurship